Exploring advanced Drosophila cell death techniques and cancer-related studies - Tendero-Lopez, Daniel; Dominguez, Maria; Uribe, Mary Luz (Frontiers in Cell Death, 2024)
Cell death is an essential physiological process for the survival of multicellular organisms. Our understanding of programmed cell death in development, immune function maintenance, and adult tissue repair has significantly advanced over the past decade. However, there are still gaps in our knowledge about the induction, regulation, and checkpoints of this process due to the diverse forms of cellular suicide and the rapid nature of the process. Molecular advancements such as specific cell death sensors, RNA-seq, single-cell RNA-seq, and metabolomics have allowed for identifying new factors and a better understanding of the molecular networks and pathways that regulate these processes. Programmed cell death also plays a role in cancer, both limiting and facilitating aspects of the malignant process, making its analysis and inhibition challenging. This review discusses the field's advancements using the model organism Drosophila melanogaster, the types of cell death in development and adult tissues, the techniques for studying it, and its role in cancer.